International Trade from Economic and Policy Perspective - Bobek, Vito (IntechOpen, 2012)
Today's international trade is radically more complex. The revolution in information and communication technologies fostered an internationalisation of supply chains which created a nexus between trade, investment, and services which is at the heart of so much of today's international commerce. The degree of recent change has created an uncertainty that now demands new global trade systems - a new set of rules for the new environment. This book tackles some of the unresolved issues in international trade that will continue to press into the next decades. Covering an array of topics critical to today's scholar, economic policy designer and business leader, the book International Trade from Economic and Policy Perspective is comprised of four sections: International Trade Theories, Trade Patterns, Government Policies and International Trade, and Business Perspective of International Trade.